2019
DOI: 10.1002/jbmr.3716
|View full text |Cite
|
Sign up to set email alerts
|

Klf4 Promotes Dentinogenesis and Odontoblastic Differentiation via Modulation of TGF-β Signaling Pathway and Interaction With Histone Acetylation

Abstract: Transcription factors bind to cell‐specific cis‐regulatory elements, such as enhancers and promoters, to initiate much of the gene expression program of different biological process. Odontoblast differentiation is a necessary step for tooth formation and is also governed by a complex gene regulatory network. Our previous in vitro experiments showed that Krüppel‐like factor 4 (KLF4) can promote odontoblastic differentiation of both mouse dental papillary cells (mDPCs) and human dental pulp cells; however, its m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 50 publications
2
72
1
Order By: Relevance
“…The data of a CHIP analysis revealed that when dental pulp cells are induced into odontoblasts, HDAC3 mainly interacts with KLF4 on the promoter of Dmp1 and Sp7 on day 0 of induction, while p300 interacts on day 7 of induction. These results reveal that KLF4 can regulate the odontoblast differentiation by affecting the histone acetylation on the promoter regions of DMP1 and Sp7 and by interacting with p300 and HDAC3 [ 134 ].…”
Section: Epigenetic Mechanisms In Dpscsmentioning
confidence: 99%
“…The data of a CHIP analysis revealed that when dental pulp cells are induced into odontoblasts, HDAC3 mainly interacts with KLF4 on the promoter of Dmp1 and Sp7 on day 0 of induction, while p300 interacts on day 7 of induction. These results reveal that KLF4 can regulate the odontoblast differentiation by affecting the histone acetylation on the promoter regions of DMP1 and Sp7 and by interacting with p300 and HDAC3 [ 134 ].…”
Section: Epigenetic Mechanisms In Dpscsmentioning
confidence: 99%
“…The deacetylation role of HDACs has been explored in cell differentiation. Our previous study showed that acetylation was involved in dentinogenesis, and HDAC3 regulated histone acetylation during odontoblast differentiation (Tao et al, 2019). HDAC6 could also deacetylate histones related to Runx2 (Ozaki et al, 2013) and acted as a co-repressor for Runx2 transcription to suppress the osteoblastic differentiation of MC3T3 cells (Zhu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For functional knock-down of HDAC6, an HDAC6-targeting small interfering RNA (siRNA; siHDAC6, Sigma) and the universal negative control siRNA were transfected into hDPCs. Cells were seeded into 6-well plates and then transfected with siRNA using Lipo2000 (Invitrogen, Thermo Fisher Scientific, Waltham, MA, United States) according to the manufacturer's instructions (Tao et al, 2019). Knockdown efficacy was confirmed by western blot.…”
Section: Small Interfering Rna and Mrfp-gfp-lc3 Plasmid Transfectionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study reported the differentiation of pulp-like tissues in a subcutaneous immunodeficient mouse model, after the implantation of human tooth root segments with 3D-DPSCs [ 2 ]. Although many groups have been studying the odontogenic differentiation [ 13 15 ], the exact molecular mechanisms are still poorly understood, and thus, the regeneration of dentin-pulp complex in the clinical context is still not implemented [ 16 ]. Therefore, the search for new biomarkers linked to the molecular mechanisms of odontogenic differentiation is extremely important for studying pulp regeneration.…”
Section: Introductionmentioning
confidence: 99%